A Student Appraisal of the Proposed Guidelines for Operations Research - Carpio, D.; Cohen, B.; Eldred, J.; Gangavane, V.; Greiner, J.; Hall, J.; Jayaraman, L. L.; Joglekar, P.; Levine, R.; Noad, A.; Prasow, S.; Sagasti, F.; et al. (Management Science, 1972)
(Foreword by Russell L. Ackoff, University of Pennsylvania) A number of my students have had their hackles up ever since the Guidelines appeared. They have been frustrated by their inability to do anything about them. Therefore, when an invitation to contribute to this discussion came to me, I asked them to substitute for me. What they have written is much more provocative and useful than, anything I could have done.